Wildfire risks under a changing climate: Synthesized assessments of wildfire risks over southwestern China - Xu, Yuanxin; Guo, Haiyan; Liu, Jia; Sun, Rui; Li, Xiaolan (Frontiers in Environmental Science, 2023)
Wildfire events in southwestern China resulted in catastrophic loss of property and human life, and the localized wildfire risks show differentiated trends under global warming scenarios. In the case of quantitating climate impacts and localizing wildfire risks, synthesized assessments of wildfire risks of high-incident areas in southwestern China are established and mapped in this article, constituted by three essential elements: hazard, vulnerability, and disaster prevention/mitigation capacity. The hazard group includes vegetation ignitability and fire spreading related to climate and topography factors. Public and economic characteristic elements belong to the vulnerability and disaster prevention/mitigation capacity group based on their functions and influences on wildfire events. Each aspect and group are rated by the historical wildfire site records and weighted by the entropy weight method and analytic hierarchy process. Assessments indicate that most very high wildfire risk girds are distributed in the west of 103°E and the north of 28°N, covering an area of over 26,500 km2, mainly in low-altitude suburban regions in basins and valleys with high climate hazards. The highly localized wildfire risk maps specified both stresses of fire prevention/mitigation in each grid cell and general spatial patterns of wildfire risks, thereby enhancing the understanding of both current and future patterns of wildfire risks and thus helping improve suppression and prevention policies.